(untitled) (Advances in Systems Science and Applications, 2023)
The active suspension system is installed in the car to improve the smoothness and comfort while driving. In this paper, a quarter-dynamic model is utilized to describe the car’s vibrations. The SM (sliding mode) control algorithm is proposed to control the operation of the suspension system. The problem’s input signal is the excitation from the road surface, while the output signal includes values related to the acceleration and displacement of the vehicle body. In addition, the interaction between the wheel and the road surface, which is expressed through the change of dynamic force, is also considered. The numerical simulation is performed with a sinusoidal pavement excitation signal. According to this result, the car body displacement was greatly reduced when using an active suspension controlled by the SM method. Meanwhile, the RMS value of acceleration is only 14.84% compared to the car using a traditional suspension system. The fluctuation of the unsprung mass is insignificant, so it does not affect the car’s smoothness. Additionally, the change in dynamic force is small, not exceeding 3.3%, when the vehicle body oscillates. This helps increase wheel stability and holding. The effect that the SM algorithm brings to this study is positive.